Enzymic removal of 5-methylcytosine from DNA by a human DNA-glycosylase. - Vairapandi, M (1993)
DNA 5-methylcytosine is a major factor in the silencing of mammalian genes; it is involved in gene expression, differentiation, embryogenesis and neoplastic transformation. A decrease in DNA 5-methylcytosine content is associated with activation of specific genes. There is much evidence indicating this to be an enzymic process, with replacement of 5-methylcytosine by cytosine. We demonstrate here enzymic release of 5-methylcytosines from DNA by a human 5-methylcytosine-DNA glycosylase activity, which affords a possible mechanism for such replacement. This activity generates promutagenic apyrimidinic sites, which can be related to the high frequency of mutations found at DNA 5-methylcytosine loci. The recovery of most released pyrimidines as thymines indicates subsequent deamination of free 5-methylcytosines by a 5-methylcytosine deaminase activity. This prevents possible recycling of 5-methylcytosine into replicative DNA synthesis via a possible 5-methyl-dCTP intermediate synthesized through the pyrimidine salvage pathway. Taken together, these findings indicate mechanisms for removal of 5-methylcytosines from DNA, hypermutability of DNA 5-methylcytosine sites, and exclusion of 5-methylcytosines from DNA during replication.